2021
DOI: 10.3389/fnins.2021.631195
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cortisol and Testosterone in Risky Decision-Making: Deciphering Male Decision-Making in the Iowa Gambling Task

Abstract: Despite the widely observed high risk-taking behaviors in males, studies using the Iowa gambling task (IGT) have suggested that males choose safe long-term rewards over risky short-term rewards. The role of sex and stress hormones in male decision-making is examined in the initial uncertainty and the latter risk phase of the IGT. The task was tested at peak hormone activity, with breath counting to facilitate cortisol regulation and its cognitive benefits. Results from IGT decision-making before and after coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Four of these studies employed the Iowa gambling task (IGT), which includes two phases (see Table 1), uncertainty ( rst block), and risk (last block), and evaluated its connection with endogenous testosterone. However, all four studies discovered no link between endogenous testosterone and uncertain decisions in the uncertainty phase (Evans & Hampson, 2014;Reavis & Overman, 2001;Singh, 2021;Stanton et al, 2011a). Among these, in the risky phase, three of the studies observed riskier decision-making in individuals with higher endogenous testosterone levels who preferred more disadvantageous card sets (Evans & Hampson, 2014;Reavis & Overman, 2001; Stanton et al, 2011a).…”
Section: Results Of Individual Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Four of these studies employed the Iowa gambling task (IGT), which includes two phases (see Table 1), uncertainty ( rst block), and risk (last block), and evaluated its connection with endogenous testosterone. However, all four studies discovered no link between endogenous testosterone and uncertain decisions in the uncertainty phase (Evans & Hampson, 2014;Reavis & Overman, 2001;Singh, 2021;Stanton et al, 2011a). Among these, in the risky phase, three of the studies observed riskier decision-making in individuals with higher endogenous testosterone levels who preferred more disadvantageous card sets (Evans & Hampson, 2014;Reavis & Overman, 2001; Stanton et al, 2011a).…”
Section: Results Of Individual Studiesmentioning
confidence: 95%
“…Among these, in the risky phase, three of the studies observed riskier decision-making in individuals with higher endogenous testosterone levels who preferred more disadvantageous card sets (Evans & Hampson, 2014;Reavis & Overman, 2001; Stanton et al, 2011a). On the contrary, the fourth study (Singh, 2021) discovered that males with higher endogenous testosterone had a better decision performance in the risky phase, i.e., choosing the advantageous card set and making less risky decisions than males with lower endogenous testosterone.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…It should be considered that other factors may play a role as well. The study using the Iowa Gambling Task showed a joint role of cortisol and testosterone in decision-making in the Singh ( 2021 ). Specifically, cortisol impaired decision-making in trials with high uncertainty, while testosterone improved decision-making in high risk trials.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous testosterone increased risk-taking in the Iowa Gambling Task (IGT) in a group of women, likely by increasing reward sensitivity while decreasing punishment sensitivity. Similarly, endogenous testosterone accounted for 11% decision-making in the uncertainty phase of the IGT (Singh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies have shown that stress with or without type 2 diabetes is associated with increased cortisol levels and lower testosterone. 6,7,8,9 CRHR1, CYP17A1, and FKBP5 are defined as stress system genes mainly expressed in the following tissues: the pituitary gland, adrenal gland, and skeletal muscle. The gene CYP17 is responsible for making an enzyme that converts cholesterol into cortisol.…”
Section: Stress Induced Cortisol Release Depresses the Secretion Of T...mentioning
confidence: 99%